Steviol glycosides affect functional properties and macromolecular expression of breast cancer cells. Issue 10 (2nd September 2022) - Velesiotis, Christos; Kanellakis, Marinos; Vynios, Demitrios H.
Abstract: Steviol glycosides, the active sweet components of stevia plant, have been recently found to possess a number of therapeutic properties, including some recorded anticancer ones against various cancer cell types (breast, ovarian, cervical, pancreatic, and colon cancer). Our aim was to investigate this anticancer potential on the two most commonly used breast cancer cell lines which differ in the phenotype and estrogen receptor (ER) status: the low metastatic, ERα+ MCF‐7 and the highly metastatic, ERα−/ERβ+ MDA‐MB‐231. Specifically, glycosides' effect was studied on cancer cells': (a) viability, (b) functionality (proliferation, migration, and adhesion), and (c) gene expression (mRNA level) of crucial molecules implicated in cancer's pathophysiology. Results showed that steviol glycosides induced cell death in both cell lines, in the first 24 hr, which was in line with the antiapoptotic BCL2 decrease. However, cells that managed to survive showcased diametrically opposite behavior. The low metastatic ERα+ MCF‐7 cells acquired an aggressive phenotype, depicted by the upregulation of all receptors and co‐receptors ( ESR, PGR, AR, GPER1, EGFR, IGF1R, CD44, SDC2, and SDC4 ), as well as VIM and MMP14 . On the contrary, the highly metastatic ERα−/ERβ+ MDA‐MB‐231 cells became less aggressive as pointed out by the respective downregulation of EGFR, IGF1R, CD44, and SDC2 . Changes observed in gene expression were compatible with altered cell functions. Glycosides increased MCF‐7 cells migration and adhesion, but reduced MDA‐MB‐231 cells migratory and metastatic potential. In conclusion, the above data clearly demonstrate that steviol glycosides have different effects on breast cancer cells according to their ER status, suggesting that steviol glycosides might be examined for their potential anticancer activity against breast cancer, especially triple negative breast cancer (TNBC).